More caseworkers shorten unemployment durations and save costs: Results from a field experiment in an Austrian public employment office - René Böheim; Rainer Eppel; Helmut Mahringer (Austrian Institute of Economic Research (WIFO), 2022)
In a randomised controlled trial in Austria, lower caseloads in public employment offices led to more meetings of the unemployed with their caseworkers, more job offers, more program assignments, and more sanctions for noncompliance with job search requirements. More intensive counselling led to shorter unemployment episodes due to faster job entry, but also to more exits from the labour force in the two years following treatment. We find effects for different subgroups of unemployed. We find no effects on wages. A cost-benefit analysis suggests that lower caseloads not only shorten the duration of unemployment but are also cost-effective.
Keywords: J64; J68; 330; Active Labour Market Policy; Public Employment Services; Caseworkers; Counseling; Job Placement; Field Experiment